Предмет: Математика,
автор: vika2283
(х-3)(х^2+3х+9)-х (^2-16)=21
Ответы
Автор ответа:
0
Первые две скобки - это формула разности кубов, исходя из этого приводим к начальному виду и вычисляем:
x^3-27-x^3+16x=21
16x-27=21
16x=21+27
16x=48
x=3
x^3-27-x^3+16x=21
16x-27=21
16x=21+27
16x=48
x=3
Автор ответа:
0
Спасибо )
Автор ответа:
0
Не за что) Удачи
Похожие вопросы
Предмет: Математика,
автор: nelyashaimova89
Предмет: Биология,
автор: zarabativaem
Предмет: Физика,
автор: ptitsachastya113
Предмет: Биология,
автор: Anony
Предмет: Алгебра,
автор: krapivinao